2014
DOI: 10.1007/978-3-319-10404-1_92
|View full text |Cite
|
Sign up to set email alerts
|

Automated 3D Segmentation of Multiple Surfaces with a Shared Hole: Segmentation of the Neural Canal Opening in SD-OCT Volumes

Abstract: The need to segment multiple interacting surfaces is a common problem in medical imaging and it is often assumed that such surfaces are continuous within the confines of the region of interest. However, in some application areas, the surfaces of interest may contain a shared hole in which the surfaces no longer exist and the exact location of the hole boundary is not known a priori. The boundary of the neural canal opening seen in spectral-domain optical coherence tomography volumes is an example of a "hole" e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Meaning that for each subject in the testing set the average of errors in the 20 slices (with BMO points manually marked on them) are computed and the standard deviation is computed over the averages of the subjects. Based on BMO identification errors, the proposed method outperformed our previous iterative approach (Antony et al, 2014) in the z -direction, r -direction, and r - z plane ( p < 0.05). Similarly, the signed BMO identification error showed that the proposed method has significantly lower errors in the r - and z -directions than the iterative approach ( p < 0.05).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Meaning that for each subject in the testing set the average of errors in the 20 slices (with BMO points manually marked on them) are computed and the standard deviation is computed over the averages of the subjects. Based on BMO identification errors, the proposed method outperformed our previous iterative approach (Antony et al, 2014) in the z -direction, r -direction, and r - z plane ( p < 0.05). Similarly, the signed BMO identification error showed that the proposed method has significantly lower errors in the r - and z -directions than the iterative approach ( p < 0.05).…”
Section: Resultsmentioning
confidence: 79%
“…The performance of the proposed BMO identification method (BMO proposed ) as well as our previous iterative method (Antony et al, 2014) (BMO iterative ) were evaluated using the reference standard obtained on the 20 slices of each subject with manual delineation (BMO manual ). The signed and unsigned distances of automated BMO points with manual BMO points in the r -direction and z- direction, were measured separately.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the retinal layers in ONH centered SD-OCT image have a shared hole. Such discontinuity makes it difficult to accurately segment the layers when the exact position of the hole boundary, i.e., the optic disc boundary are not known a priori [19]. For decades, several studies were devoted to OCT image layer segmentation and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A graph cut-based segmentation method was proposed for simultaneous segmentation of multiple 3-D surfaces in the macula 24 and optic nerve head. 25 However, the minimum cut graph algorithm is computationally expensive which usually requires minutes to complete a 3-D data segmentation. Cheng and Lin 26 proposed a fast 3-D dynamic programming expansion method for vessel boundary detection on magnetic resonance imaging sequences.…”
mentioning
confidence: 99%